Understanding urban government : metropolitan reform reconsidered - Bish, Robert L.; Ostrom, Vincent (Washington, American Enterprise Institute for Public Policy Research, 1970)
It provides an introduction to "public choice" analysis of urban problems. The book reveals some of the problem associated with basic concepts used in the traditional approach tp metropolitan reform.
Includes bibliographical references.
occ 15/01/2019
Loans
Keywords: Municipal government; Municipal services; Metropolitan government; Urban government